(untitled) (Bulletin of Innovative Research, 2026)
The article presents a psycholinguistic analysis of speech disorders observed in aphasia at different levels of the speech system. The aim of the study is to identify speech impairments characteristic of aphasia at the phonetic-phonological, lexical-semantic, and grammatical levels, and to explain their underlying mechanisms within a psycholinguistic framework. The research theoretically substantiates the multi-stage structure of speech activity, the processes of linguistic unit processing, as well as the mechanisms of speech production and comprehension.